Winds at the Mars 2020 Landing Site: 1. Near‐Surface Wind Patterns at Jezero Crater. Issue 12 (9th December 2022) - Viúdez‐Moreiras, D.; Lemmon, M.; Newman, C. E.; Guzewich, S.; Mischna, M.; Gómez‐Elvira, J.; Herkenhoff, K.; Sánchez‐Lavega, A.; de la Torre, M.; Rodríguez‐Manfredi, J. A.; Lorenz, R. D.; Pla‐García, J.; et al.
Abstract: This is the first part of a two‐part paper. NASA's Mars 2020 Perseverance rover measured winds on the Jezero crater floor close to the delta of an ancient river. A mostly repeatable diurnal cycle was observed and presented two regimes: (a) a convective regime, from dawn to sunset, with average easterly to southeasterly winds, during which maximum wind speeds were measured, and (b) a nighttime regime with westerly‐northwesterly winds followed by a relatively calm period with highly variable wind directions as a function of sol and time of night. The timing and magnitude of the observed regimes are consistent with primary control by regional and local slope flows. Data suggest that the surface circulation at Jezero region in northern spring and summer is highly unaffected by large‐scale circulation except during particular periods in the diurnal cycle or generally during dust storms, which is supported by MarsWRF model simulations. Consequently, the observed seasonal variability was weak. However, sol‐to‐sol and seasonal variability were measured, most of it during certain nighttime periods. Traveling waves consistent with baroclinic instability were clearly observed in surface winds at L s ∼ 75°. The early MY36/2022A regional dust storm at L s ∼ 153° disturbed the wind patterns with changes suggesting enhanced tidal flows. After sunset, the dust storm also produced detectable gravity wave activity, increasing the mixing in the nighttime planetary boundary layer during storm conditions. Inferred wind directions from dust devil movies strongly suggest that prevailing winds continued to be slope‐driven during the late summer, fall and early winter seasons. Plain Language Summary: This is the first part of a two‐part paper. NASA's Mars 2020 Perseverance rover landed close to the western rim of Jezero crater (18.44°N, 77.45°E) on 18 February 2021. The wind data acquired by the rover measured a mostly repeatable diurnal cycle with two regimes: (a) a convective period, from dawn to sunset with average easterly to southeasterly winds, in which maximum wind speeds were measured, and (b) a nighttime regime with westerly‐northwesterly winds followed by a relatively calm period with highly variable wind directions as a function of sol and time of night. The timing and magnitude of the observed regimes are consistent with primary control by regional and local slope flows, as have been observed to varying degrees at other landing sites on Mars. Data suggest that the surface circulation at Jezero is highly unaffected by large‐scale circulation, except during particular periods. An early regional dust storm prior to fall equinox also disturbed wind patterns with changes suggesting the strengthening of flows linked to large‐scale atmospheric oscillations called tides. The latter are primarily driven by the daily pattern of solar heating around Mars and its interaction with topography. Key Points: A mostly repeatable diurnal cycle of winds is consistent with primary control by regional and local slope flows Great sub‐diurnal and sol‐to‐sol variability in winds was observed during the calm period at night Traveling and gravity waves were observed, along with the probable effect of enhanced tidal flows